Interventions and development strategies towards intensive social support among the participants of activity center for older adults in Malaysia. Issue 2 (25th March 2022) - Zainuddin, Faizah Hanim; Hamidi, Mashitah; Wahab, Haris Abd
Abstract: Social support is essential for improving the lives of older adults. However, some respondents of other literature reported receiving less adequate financial support from family, a lack of comprehensive policies to protect older adults, and a smaller social network as they age. In order to address this issue, more intense social support is required as older adults are at risk of obtaining insufficient social support from their social network. Therefore, this study aimed to explore the interventions and development strategies for social support for older adults. The qualitative case study method was used in this study, and in‐depth interviews were conducted with 24 older adults aged 60 and above who participated in Pusat Aktiviti Warga Emas (PAWE), an activity center for older adults, for more than 5 months. Four PAWE supervisors and three policymakers from Department of Social Welfare Malaysia (JKMM) were also interviewed. The data were then thematically analyzed. The study highlighted three intervention and development strategies to improve social support for older adults namely in the areas of personal development, policy, and social connectivity of older adults. As Malaysia is expected to become an aging population by 2035, it is vital to establish a supportive environment for older people.